Internalisasi Nilai-Nilai Karakter Dalam Proses Pembelajaran Untuk Membentuk Karakter Peserta Didik - Darnanengsih Darnanengsih; Rusyaid Rusyaid (LPPM IAIN Sorong, 2020)
This paper found that the character of education at Averos High School was successfully implemented since in 2010. The implementation of character education was carried out through the internalization of character values in the syllabus and lesson plans. The character values were explicitly taught in teaching activities that include in initial, core and closing activities. In addition, the implementation of character education was carried out with exemplary and habituation that were integrated in daily life of student. The character education was both taught in class and practically implemented outside the classroom through extracurricular activities. Furthermore, the implementation of the character education was examined through three aspects, namely cognitive, affective, and psychomotor aspect. The assessment through these three aspects was carried out continuously in formal learning activities in the classroom and outside the classroom. Finally, the study also reported some factors supporting the internalization of character values, namely family, the headmaster, educators, environment and facilities while time that student spending in the school, and community participation were reported as constraints